PENGARUH OPINI AUDIT DAN KESULITAN KEUANGAN TERHADAP AUDIT DELAY - Nadhifah, Ghina Fairuz; Suherman, Acep; Eriswanto, Elan (Universitas Muhammadiyah Tangerang, 2023)
The purpose of this study is to determine the influence of Audit Opinion, Financial Difficulties on Audit Delay. Variables in this study are Opinion Audit, Financial Difficulty and Audit Delay. This reseach was a quantitative research. Use secondary data obtained from www.idx.co.id as a data source. The population in this study is Property and Real Estate companies listed on the Indonesia Stock Exchange in 2018 – 2019. While the samples in this study were determined using purposive sampling method and obtained 90 data of financial statements of Property and Real Estate companies that meet the criteria. This study uses multiple linear regression analysis. The results of this study showed that the significant value of Audit Opinion is 0.000 and tcount is -3,732 which means that the Audit Opinion partially negatively and significantly influenced the Audit Delay and the value of financial difficulty significance is 0.794 and the tcount value is -0.262 which means that Financial Difficulty has no significant effect on Audit Delay. While the results of the significance of audit opinion and financial difficulties simultaneously to audit delay is 0.001 and Fcount is 7,102 which indicates that Audit Opinion and Financial Distress simultaneously have a significant effect on Audit Delay. Keywords: Opinion Audit, Financial Distress, Audit Delay